2014
DOI: 10.1002/tl.20083
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Classrooms and Educational Alliances: Changing Relationships to Improve Learning

Abstract: This chapter explores the “educational alliance” among students and between students and instructors. We contend that this is a framework that can help us understand how active learning classrooms facilitate positive educational outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 13 publications
2
50
0
2
Order By: Relevance
“…Based on active learning, it can be found that students also learn responsibility among individuals and groups in solving the problem. As confirmed by Baepler & Walker [3] that active learning in groups can assign students to take responsibility for their self and their group due to the task they have.…”
Section: B Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Based on active learning, it can be found that students also learn responsibility among individuals and groups in solving the problem. As confirmed by Baepler & Walker [3] that active learning in groups can assign students to take responsibility for their self and their group due to the task they have.…”
Section: B Discussionmentioning
confidence: 86%
“…The use of this method, students usually will feel the environment to be more fun, so their learning achievement can be maximized. It is corresponding to Baepler & Walker research [3] that class which uses active learning will generate positive education. That matter happens because of the active learning constitutes one of the learning processes that involves physic effectively that gives effect for students in learning achievement [9] [17].…”
Section: B Active Learningmentioning
confidence: 99%
“…Comprehensive or simplified sets of questions have been asked to measure rapport in those studies [29,30], but in this study we directly asked students to gauge perceived rapport in a single question. Others described this concept as educational alliance or reduction of psychological distance that leads to improved outcomes [31][32][33]. Overall, fostering social connectedness, particularly rapport between students and faculty in today's online society, was a main goal of creating the FB discussion group in this study.…”
Section: Need For a New Venue To Foster Learner-teacher Relationshipmentioning
confidence: 89%
“…This has changed everything for me. (Monica, novice instructor) Over the past 20 years, researcher interest in the impact of space on teaching and learning has grown (Baepler & Walker, 2014;Beichner, 2014;Brooks, 2011;Granito & Santana, 2016;Jamieson, 2003;Temple, 2008), even to the point of prompting an annual "International Forum on Active Learning Classrooms" conference at the University of Minnesota (inaugurated in 2011) and warranting a journal dedicated solely to this issue, with the Journal of Learning Spaces launched in 2011. A driver for this interest is research that exposes the limitations of the conventional lecture.…”
mentioning
confidence: 99%